Qualidade de vida no trabalho e vínculos organizacionais: um estudo com profissionais da Estratégia Saúde da Família em Manaus (AM) - Mirian Serrão Vital (2019)
Considered both a contemporary phenomena, Quality of Work Life (QWL) and Organizational Linkages (commitment, entrenchment and consent) have been studied independently, despite localized research efforts on relations between QWL and the organizational commitment bonds. Stands out that no national and international studies that contemplated relations between QWL and the bonds of commitment, entrenchment and consent in an integrated way were found, which was performed in this thesis. For the area of people management and organizational behavior, QWL aims to provide well-being and job satisfaction, leading to greater productivity. The organizational bonds link individuals to organizations and influence their attitudes and behaviors. The objective of this research was to identify and analyze, together with doctors and nurses of the Family Health Strategy (FHS) in Manaus (AM), the relationship between Quality of Life at Work (QWL) and Organizational Bonds (commitment, entrenchment and consent). The methodological, quantitative, descriptive and field study approach was developed through case study. The field research approached 161 professionals (98 nurses and 63 doctors) through a questionnaire. The data analysis involved exploratory factor analysis, structural equation modeling and descriptive data analysis. Among the main results, stands out the proposition of an unprecedented relational model, consisting of 10 constructs and 39 observed variables. Furthermore, it is noticed that the relevant findings of this thesis demonstrated that the constructs of quality of work life, validated by the respondent data (Specific satisfactions: Rewards and Supervision; Task dimensions: Autonomy and Communication), influence the three bonds and ultimately determine compliance with the rules, including submission to the hierarchy, culminating in Organizational Consent. The analysis process and these results enable future researches